Photoelectric and diffusion charging measurements of fine particulate air pollution along the main roads of the city of Madrid from 1999 to 2021. (1st August 2022) - Siegmann, Philip; Gómez-Moreno, Hilario
Abstract: In this work, the evolution of the fine particulate air pollution (of size below one μm) produced by the vehicles when driving along several roads of Madrid is studied. Measurements were taken with portable near real-time sensors of Diffusion Charging (DC) and Photoelectric Charging (PC) while driving along the roads. The obtained measurement profiles basically consist of spikes when measuring in the exhaust plumes of preceding vehicles and a background level of mixed aged exhaust that forms when high traffic intensity exist. The DC sensor measures air concentration of the particles Total Active Surface (TAS) and the PC sensor was calibrated to measure the air concentration of Particle bound Polycyclic Aromatic Hydrocarbons (PPAH). The amount of adsorbed PAH per active surface (the PC/DC ratio) is a measure of particles toxicity. Both sensors are sensible to ultra-fine particles of size below 0.1 μm. The measured median values of DC and PC, for the years 1999, 2001, 2005, 2006, 2016, 2017, 2020 and 2021, are plotted as well as their median PC/DC ratio. Examples of measurement profiles are also shown including measurements during COVID-19 driving restrictions. During these restrictions, we could conclude that our measured particulate air pollution of fine and ultrafine particles is caused by "polluting-vehicles" still coexisting in the vehicle fleet of Madrid, which do not fulfill the latest Euro standard because they are too old or have no/malfunctioning catalytic converter and/or diesel particle filter (DPF). The changes of the measured median of the DC and PC values are discussed based on already known results of implemented vehicle technologies for reducing emissions, the evolution of the vehicle fleet fulfilling the increasingly demanding Euro standards, the traffic count, the PC and DC working principles, the evolution of the exhaust emission when exiting the pipe, and on the sulfur content reductions in diesel. The main factors that allowed the large reduction of the median values of both DC and PC (from 1167 ± 57 mm 2 /m 3 and 990 ± 54 ng/m 3 in 1999 to 263 ± 14 mm 2 /m 3 and 124 ± 7 ng/m 3 in 2021 respectively) as well as the changes in the PC/DC ratio was, according to our findings, the diesel sulfur content reduction and the implementation of the Diesel Oxidation Catalysis (DOC) and the DPF. Highlights: Decrease in the total active surface of fine particles in the air of the city of Madrid since 1999. Decrease in PAH adsorbed on fine particles in the air along the roads of the city of Madrid since 1999. Evolution of on-road fine and ultrafine exhaust particle emissions in Madrid since 1999. Drastic localized increase of air suspended fine particles caused by specific polluting vehicles. Changes in the on-road fine and ultrafine exhaust particles toxicity in Madrid since 1999.